Development of a contacting transwell co-culture system for the in vitro propagation of primary central nervous system lymphoma - Nishi, Mayuko; Tateishi, Kensuke; Sundararaj, Jeremiah Stanleyraj; Ino, Yoko; Nakai, Yusuke; Hatayama, Yasuyoshi; Yamaoka, Yutaro; Mihana, Yusaku; Miyakawa, Kei; Kimura, Hirokazu; Kimura, Yayoi; Yamamoto, Tetsuya; et al. (Frontiers in Cell and Developmental Biology, 2023)
Primary central nervous system lymphoma (PCNSL) is a malignant neoplasm of the central nervous system that is refractory to treatment and has extremely poor prognosis. One factor hindering the development of therapeutic options for PCNSL is its molecular heterogeneity and the extreme difficulty in establishing in vitro cell lines that permit intensive research on this disease. In the present study, we developed a method to propagate PCNSL cells in vitro using a contacting transwell cell culture system involving brain vascular pericytes. The co-culture system was found to recapitulate the tumor microenvironment that is influenced by the biological activity of adjacent pericytes, and to sustain the survival and proliferation of PCNSL cells in vitro. We further delineated the underlying molecular mechanisms and found that the HGF–c-Met axis may be involved in the long-term in vitro culture of PCNSL cells. Moreover, the peptidylprolyl isomerase Pin1 was found to play a key role in PCNSL cell survival and it sustained proliferation through interactions with key transcription factors related to B-cell lymphomagenesis. These results suggest that our in vitro co-culture system is well suited to analyzing the biological and molecular characteristics of PCNSL, and may contribute to the discovery of new therapeutic interventions.